New Directions in Understanding Atopic March Starting from Atopic Dermatitis - Nunzia Maiello; Pasquale Comberiati; Arianna Giannetti; Giampaolo Ricci; Rossella Carello; Elena Galli (MDPI AG, 2022)
Recent evidence showed that the postulated linear progression of the atopic march, from atopic dermatitis to food and respiratory allergies, does not capture the heterogeneity of allergic phenotypes, which are influenced by complex interactions between environmental, genetic, and psychosocial factors. Indeed, multiple atopic trajectories are possible in addition to the classic atopic march. Nevertheless, atopic dermatitis is often the first manifestation of an atopic march. Improved understanding of atopic dermatitis pathogenesis is warranted as this could represent a turning point in the prevention of atopic march. In this review, we outline the recent findings on the pathogenetic mechanisms leading to atopic dermatitis that could be targeted by intervention strategies for the prevention of atopic march.